(untitled) (Sebha University Conference Proceedings, 2024)
This study explores the effects of cellulose derived from olive kernels (OK) and olive pomace (OP) on the properties of drilling fluids. The analysis revealed that both OK and OP cellulose exhibit similar density values across identical concentrations, indicating consistent density properties under the tested conditions. In terms of plastic viscosity (P.V.), OP cellulose demonstrated a slightly higher value of 10.4 cp compared to 10 cp for OK cellulose at a concentration of 0.1%, suggesting that both may be nearing a plasticity threshold where cellulose particle aggregation reduces thickening efficiency. Apparent viscosity (A.V.) peaked at 16.5 for OK and 15 for OP at a 0.1% concentration, illustrating distinct shear-thinning behaviours where viscosity decreased with increased shear rates at higher concentrations. Further, yield strength was found to be concentration-dependent, with OK cellulose peaking at 0.05% and OP cellulose at 0.1%. Filtration efficiency was notably improved by the addition of natural cellulose, with the highest filtration results observed at concentrations of 0.4% and 0.25%, achieving a value of 11.5 for both OK and OP cellulose. This suggests that increasing cellulose concentration can positively impact filtration control. The consistent performance of OP cellulose across various concentrations highlights its stability in enhancing filtration properties. Overall, the differences in cellulose behaviour between OK and OP are likely due to their unique physical properties, influencing their performance in drilling fluids.